Relationship help-seeking and the health belief model: how the perception of threats and expectations are associated with help-seeking behavior - Hubbard, Aimee K. (Kansas State University, 2017)
Couples often wait until the very end to seek help for their relationship, with divorce being one of the primary concerns cited in couple’s therapy (Doss, Simpson & Christensen, 2004). While couples appear to be reluctant to seek formal resources, we know that over 50% of individuals are confiding in friends and family about their relationship (Lind Seal, Doherty, & Harris, 2015). Currently, the literature is limited and unable to provide a comprehensive explanation for why individuals do or do not seek help for their relationship. Using an interdisciplinary approach, we adapted a medical model- the Health Belief Model (HBM)- to relationship help-seeking. Based on the success of this model at predicting help-seeking behaviors related to physical and mental health, we believe it could be applicable to relationship help-seeking. In addition to identify factors associated with relationship help-seeking behaviors, we hope to identify factors that mediate both formal and informal relationship help-seeking behaviors. To study this we collected data from 347 individuals in emotionally committed relationships. The results of the analysis showed that the perception of threats, such as greater relationship instability and greater negative social comparison, were linked to more online help-seeking; whereas expectations such as the greater endorsement of stigma of self and masculinity were linked to lower levels relationship help-seeking behaviors and worse attitudes toward help-seeking. Furthermore, greater stigma of self was found to be directly linked to having a worse attitude toward help-seeking, as well as indirectly linked to lower rates of formal and online relationship help-seeking behaviors via the prior effects of attitudes toward help-seeking. The results of this study suggest further areas for investigation in regard to relationship help-seeking, specifically around self-stigma.
Keywords: Health Belief Model; Relationship help-seeking